The relationship of dehydration and body mass index with the occurrence of atrial fibrillation in heart failure patients. (14th October 2021) - Chuda, A; Kaszkowiak, M; Banach, M; Maciejewski, M; Bielecka-Dabrowa, A
Abstract: Background/Introduction: Heart failure (HF) and atrial fibrillation (AF) are two conditions that are likely to dominate the next years of cardiovascular (CV) care. These diseases frequently coexist and they can beget one another due to similar risk factors and similar pathophysiology. Purpose: The aim of the study was to assess the relationship of dehydration, body mass index (BMI) and other indices with the occurrence of AF in HF patients. Methods: The study included 113 patients [median age 64 years; 57.52% male] hospitalized due to HF. Baseline demographics, body mass analysis, echocardiographic results, key cardiopulmonary exercise test (CPET) parameters, six minute walk distance (6MWD) and Kansas City Cardiomyopathy Questionnaire (KCCQ) score were assessed. Results: Of all patients, 23 (20.35%) had AF, and 90 (79.65%) had sinus rhythm (SR). Patients with AF were older (med. 66 vs 64 years; p=0.039), with higher BMI (32.02 vs. 28.51 kg/m 2 ; p=0.017) and percentage of fat content (37.0 vs. 27.9%, p=0.014). They were more dehydrated, with a lower percentage of total body water (TBW%) (45.7 vs 50.0%; p=0.022). Clinically, patients with AF had more often higher New York Heart Association (NYHA) class (III vs II; p<0.001), shorter 6MWD (median 292.35 vs 378.4 m; p=0.001) and a lower KCCQ overall summary score (52.60 vs 73.96 points; p=0.002). Patients with AF had significantly lower exercise capacity as measured by peak oxygen consumption (peak VO2) (0.92 vs 1.26 mL/min, p=0.016), peak VO2/kg (11 vs. 15 mL/kg/min; p<0.001), and percentage of predicted VO2max (pp-peak VO2) (62.5 vs 70.0; p=0.010). We also found VE/VCO2 (med.33.85 vs 32.20; p=0.049) to be higher and peak oxygen pulse (8.5 vs 11 mL/beat; p=0.038) to be lower in patients with AF than in patients without AF. In a multiple logistic regression model higher BMI (OR 1.23 per unit increase, p<0.001) and higher left atrial volume index (LAVI) (OR 1.07 per unit increase, p=0.03), lower tricuspid annular plane systolic excursion (TAPSE) (OR 0.74 per unit increase, p=0.03) and lower TBW% in body mass analysis (OR 0.90 per unit increase, p=0.03) were independently related to AF in patients with HF. Conclusions: Increased volume of left atrium and right ventricular systolic dysfunction are well-known predictors of AF occurrence in patients with HF, but hydration status and increased body mass also seem to be important factors of AF in HF patients. Funding Acknowledgement: Type of funding sources: None.